The Effect of Concept Attainment Model on the Academic Achievement of Physics Students on Secondary Level in Balochistan - Muhammad Asif Khan (JSE, 2024)
The concept attainment model is method of which engage the student to define the topics from their own self giving reasonable examples and evidence based analyzing the concepts through this model. Students have critical skills development and have the ability of analyzing different things. The study was compared based on pre and post assessment, survey was also conducted with concept mapping activities to know the effectiveness of the concept attainment model difference with non-concept method. Students understanding physics concept, critical thinking skill, analyzing skills, attitude and motivation were assessed by the multiple questioners’ survey. The survey data showing that student’s level of understanding of the concepts and critical thinking skills did increase with the use of the concept attainment model. Students ‘attitude and motivation were increased during the treatment units as many students perceived the concept attainment activities as being a game. The Concept attainment model is an effective teaching method to engage students in creating their own definition. The lesson helped to increase understanding of the concept and link the concept, engages students to know and think about the learning with positive effect on their attitude and motivation in class, finally CAM is the most effective model for conceptual understanding and for critical thinking in physics.